ASSESSMENT OF DRY WEIGHT PROTEIN CONTENT IN FRUIT BODY AND STIPE OF Agaricus bisporus USING IT AS A FISH FEED TO ASSESS GROWTH OF Oreochromis mossambicus - ANSARI, TASMI; JADHAV, RAHUL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The purpose of this study was to evaluate dry weight protein estimation in mushroom Agaricus bisporus and feeding that to Oreochromis mossambicus to evaluate its growth performance with respect to length and weight so as to provide a systematic basis for the effective active application of mushrooms are considered as potential source of protein.As the fruit body (the umbrella shaped body of a mushroom and stipe(Stem or stalk of mushroom supporting the cap of mushroom.) are different parts of Mushrooms has different protein content. Fruit body and stipe enriched diet was fed to Oreochromis mossambicusand the study reveals that protein content of fruit body is significantly higher than the stipe, which is 27.8% and 19.78% respectively and hence Oreochromis mossambicus growth performance is greater when fed with fruit-body enriched diet.